The Slug Mite Riccardoella (Proriccardoella) oudemansi (Prostigmata, Ereynetidae) from Ukraine - Zabludovskaya, S.A.; Badanin, I.V. (Вестник зоологии, 2010)
The mite Riccardoella (Proriccardoella) oudemansi (Prostigmata, Ereynetidae) parasitizing the lung mollusks, is redescribed based on numerous specimens from Ukraine. These mites were first found in the fauna of Ukraine in the early 1990th.